Treatment of high-strength wastewater from spoiled dairy products using anaerobic digestion with methane capture - Khin Hnin Yu (College of Engineering, University of the Philippines Diliman, 2014)
In the Philippines, the abundance of rainfall that supports pasture growth coupled with extensive grasslands and numerous technical experts sustain the coupled with development of the Philippines dairy manufacturing industry. Consequently, this causes an increase in the volume of expired dairy products. It is therefore necessary to properly treat the expired dairy products particularly those from the manufacturing process prior to disposal in order to avoid causing pollution. Dairy waste waters have high organic content and methane is generated from its anaerobic digestion. This research was conducted not only to treat the high-strength dairy Three wastewater but also capture methane gas generated from the treatment. Three experimental runs with five different dairy wastewaters were conducted for 14 days each. Anaerobic digestion of the wastewaters was operated in glass bottles containing1,000 ml of each sample. Methane generated was collected and the volume was measured via water displacement. Characterization of five kinds of dairy wastewater and quantification of methane gas produced from the treatment using anaerobic digestion batch process were also performed. Methane gas generations mainly occurred within the first seven days after which the gas generation during the treatment process slowed down. Methane capture was maximum at the last experimental run achieving an average displaced water volume of 472 ml., The analyses prove that dairy wastewaters that generate methane gas have very high concentrations of Chemical Oxygen Demand, Biochemical Oxygen Demand and Fats, Oil and Grease.